2008
DOI: 10.1016/j.fct.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and pharmacokinetics of 1-methyl-d-tryptophan: Absence of toxicity due to saturating absorption

Abstract: Abstract1-methyl-D-tryptophan (D-1MT) reverses the immunosuppressive effect of indoleamine 2,3-dioxygenase (IDO), and it is currently being developed both as a vaccine adjuvant and as an immunotherapeutic agent for combination with chemotherapy. The present study examined the pharmacokinetics and toxicity of D-1MT in preparation for clinical trials. Incubation of D-1MT in rat plasma for 24 h produced no significant degradation, with <15% of D-1MT being bound to plasma protein. Following oral administration, D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 31 publications
6
75
0
1
Order By: Relevance
“…Some drugs considered CYP substrates did not show the concentration-related stability under the same condition [18]. Drugs that are not the substrates of CYPs are usually stable in microsomal incubation and their stability will not be affected by their incubating concentrations [25]. It is prudent to set up at least two concentrations of a test drug (e.g., 1 and 10 μM) to determine if the drug's concentration has any effect on its own stability in microsomes and other biomatrices.…”
Section: Metabolism By Microsomesmentioning
confidence: 99%
“…Some drugs considered CYP substrates did not show the concentration-related stability under the same condition [18]. Drugs that are not the substrates of CYPs are usually stable in microsomal incubation and their stability will not be affected by their incubating concentrations [25]. It is prudent to set up at least two concentrations of a test drug (e.g., 1 and 10 μM) to determine if the drug's concentration has any effect on its own stability in microsomes and other biomatrices.…”
Section: Metabolism By Microsomesmentioning
confidence: 99%
“…53 1-MT appears to have little, if any, toxicity issues and is currently being developed for use as a vaccine adjuvant and combination chemotherapeutic agent. 54 However, further insight into the role of downstream kynurenine pathway metabolites in this pathophysiological process is still needed to fully understand this longstanding and very complex process.…”
mentioning
confidence: 99%
“…The authors also reported that the in vivo effects were IDO-gene dependent and concluded that 1-D-MT is the suitable choice of IDO inhibitor to be incorporated into human chemo-immunotherapy regimens. Subsequent evaluation of pharmacokinetics and toxicity of oral 1-D-MT in rats and dogs revealed that the application of 1-D-MT is safe with very little toxicity (Jia et al 2008 ). Yet, Löb et al and Qian et al suggested that 1-L-MT is more benefi cial than 1-D-MT in reversing IDO-mediated proliferation arrest and tryptophan depletion (Lob et al 2009 ;Qian et al 2009 ).…”
Section: The Use Of Ido Inhibitors With Chemotherapy And/or Tumor Vacmentioning
confidence: 98%